Marketing of Arabica Coffee by Farmer Producer Organisations (FPO’s) in Tribal Areas of Alluri Sita Rama Raju District in Andhra Pradesh - Keerthana, K.; Rani, Seedari Ujwala; Reddy, P. Pedda Nagi; Naidu, G. Mohan; Kishore, M. Ravi; Naik, B. N. Sandeep; Rao, P. Joga (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the agricultural year, 2024 to 2025 at Alluri Sita Rama Raju District (ASR), Andhra Pradesh, India to study the Marketing of Arabica Coffee by Farmer-Producer Organisations (FPOs). Three FPOs from the three selected mandals from study area were selected such as Dhimsa Natural Farming FPO in Araku Valley, Paderu Farmers Producer Company Ltd in Paderu and Maa Thota Tribal Farming & Marketing Producer Co. Ltd in Chinthaplle. It is analysed that, the total cost incurred by FPO Beneficiary for four years was ` 2,12,500 and non-beneficiary was ` 3,00,500. The total yield obtained at 5th year to FPO beneficiaries was 3400 kg ha-1 where whereas for the non-beneficiary was 2050 kg ha-1. The average selling price by FPO beneficiary to consumers was ` 700 kg-1, which was higher than selling price by non- beneficiaries (` 480). The percentage age of profit margin for beneficiary is 91.07 whereas for the non-beneficiary is 69.46. The analysis of marketing channels showed that FPOs create significant value post-harvest. Maa Thota FPO demonstrated the highest marketing efficiency (Conventional Index: 2.29 for parchment) and achieved the highest final consumer price (` 700 kg-1 for parchment). Interestingly, Paderu FPO, while less efficient, provided farmers with the highest share of the consumer’s rupee (40.74%), indicating a more equitable distribution of value. FPO beneficiaries reported better yields, income, training and access to markets after joined in group.